Research on school organizational change and its performance - Liu, Fangfei; Mahmood, Nik Hasnaa Nik (Journal of Posthumanism, 2025)
Evaluating the performance of organizational change in schools is not merely a routine aspect of the process; it is a critical factor in fostering sustainable development within educational institutions. This paper examines the concept of performance in the context of learning-driven organizational change and discusses various evaluation methods for assessing school transformations. These methods include portfolio evaluation, authentic assessment, value-added evaluation, and index evaluation. Additionally, the paper provides thoughtful recommendations and suggestions for enhancing the effectiveness of these evaluation approaches.